Electrocardiography Parameters Changes in Epilepsy and Febrile Convulsion Children Compared with Controls - Noori, Noor Mohammad; Teimouri, Alireza; Khajeh, Ali (Journal of Pediatric Epilepsy, 2020)
Epilepsy and febrile convulsion are the most common neurological diseases with significant effect on cardiac functions. This study aimed to evaluate electrocardiography parameters alterations in epilepsy and febrile convulsion children compared with controls. In this comparison study, 270 children analyzed who shared equally in epilepsy, febrile convulsion, and healthy that aged from 0.5 to 5 years. The participants were collected from Ali ibn Abi Talib Hospital of Zahedan, Iran. Epilepsy confirmed based on definition of having at least two unprovoked seizures in 24 hours. Febrile convulsion was confirmed based on its definition by the International League against Epilepsy. Healthy children selected from those referred to the hospital with fever and without any underline diseases. Electrocardiography was performed by a pediatric cardiologist. Data were analyzed using SPSS 19 with p < 0.05 significant level. Heart rate was higher in epilepsy (129.64 ± 27.63) compared with control (108.78 ± 26.01) and febrile convulsion (125.79 ± 25.38; X2 = 28.701, p < 0.001). S wave in lead V1 was higher in controls (0.72 ± 0.36) compared with epilepsy (0.58 ± 0.45) and febrile convulsion (0.58 ± 0.36). QT dispersion and QTc dispersion levels were higher in epilepsy than febrile convulsion children that both were higher than controls. Concluded that R in aVL, LV mass (LVM), QT dispersion, and QTc dispersion were higher significantly in epilepsy compared with febrile convulsion children. To maintain a good strategic treatment in patients with epilepsy and febrile convulsion, there is a need to assess alternations in ECG parameters, especially QT interval changes that lead to better comprehensive autonomic changes.
Keywords: electrocardiography; epilepsy; febrile convulsion; children